Introduction to wireless localization : with iPhone SDK examples - Chan, Eddie C. L.; Baciu, George, 1961- (Singapore : IEEE ; Wiley, 2012)
"This book provides a comprehensive overview of the entire landscape of both outdoor and indoor wireless positioning, and guides the reader step by step in the implementation of wireless positioning applications on the iPhone. Explanations of fundamental positioning techniques are given throughout the text, along with many programming examples, providing the reader with an independent, practical, and enjoyable learning of the material while gaining a real feel for the subject. Provides an accessible introduction to positioning technologies such as Global Positioning System and Wi-Fi positioning. Presents hands-on skills to iOS 5.0 programming for location-aware applications. Gives a thorough grounding in signal propagation, line-of-sight and interference effects for accurate positioning. Covers the location-aware video streaming and conferencing with practical iPhone application examples."--Publisher's website.
Introduction to Wireless Localization -- Wi-Fi Positioning Systems. Installation of Wi-Fi Infrastructure -- Algorithms Used in Wi-Fi Positioning Systems -- Implementation of Wi-Fi Positioning in iPhone -- Positioning across Different Mobile Platform -- Wi-Fi Signal Visualization -- Introduction of Global Positioning System -- Study of GPS Signal and Algorithms -- Differential GPS and Assisted GPS -- Other Existing Positioning Systems -- AI for Location-Aware Applications -- Beyond Positioning: Video Streaming and Conferencing -- Appendix A: Starting the iOS SDK -- Appendix B: Introduction to Objective-C Programming in iPhone -- Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Location-based services; Wireless localization; iPhone (Smartphone) -- Programming; TECHNOLOGY & ENGINEERING -- Radio; TECHNOLOGY & ENGINEERING -- Mobile & Wireless Communications; Wireless localization; Electronic books; Electronic books